2011
DOI: 10.1074/mcp.m111.008094
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Adipose Tissue from Zmpste24−/− Mice, a Model of Lipodystrophy and Premature Aging, Reveals Major Changes in Mitochondrial Function and Vimentin Processing

Abstract: Lipodystrophy is a major disease involving severe alterations of adipose tissue distribution and metabolism. Mutations in genes encoding the nuclear envelope protein lamin A or its processing enzyme, the metalloproteinase Zmpste24, cause diverse human progeroid syndromes that are commonly characterized by a selective loss of adipose tissue. Similarly to humans, mice deficient in Zmpste24 accumulate prelamin A and display phenotypic features of accelerated aging, including lipodystrophy. Herein, we report the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 70 publications
4
54
0
Order By: Relevance
“…The phenomenon can be reversed by raising NAD+ levels [340]. Transcription of genes encoding mitochondrial proteins is impaired during laminopathies leading to an imbalance between mitochondrial and nuclear proteins especially those constituting complexes I, III and IV of the respiratory chain and the ATPsynthase [341][342][343]. This imbalance triggers the mitochondrial unfolded protein response (UPRmt) [344], whereby mitochondria send a signal to the nucleus to induce the production of stress-related proteins, which restore the mitochondrial balance.…”
Section: Mitochondria Endoplasmic Reticulum Oxidative Stress and Numentioning
confidence: 99%
“…The phenomenon can be reversed by raising NAD+ levels [340]. Transcription of genes encoding mitochondrial proteins is impaired during laminopathies leading to an imbalance between mitochondrial and nuclear proteins especially those constituting complexes I, III and IV of the respiratory chain and the ATPsynthase [341][342][343]. This imbalance triggers the mitochondrial unfolded protein response (UPRmt) [344], whereby mitochondria send a signal to the nucleus to induce the production of stress-related proteins, which restore the mitochondrial balance.…”
Section: Mitochondria Endoplasmic Reticulum Oxidative Stress and Numentioning
confidence: 99%
“…The latter phenomenon is conserved in species from worms to humans and can be rescued by caloric restriction, suggesting it plays an important role in the regulation of longevity. Here, we created 2 mouse models to explore the role of the de- ipose tissue can also lead to accelerated aging and lipodystrophy (63,64). We now find that dicer is downregulated in the adipose tissue of patients with HIV and HIV-related partial lipodystrophy, and these individuals may exhibit signs of premature aging, metabolic syndrome (diabetes and dyslipidemia), cardiovascular disease, and increased sensitivity to stress (38).…”
Section: Discussionmentioning
confidence: 99%
“…52 The alteration of mitochondrial metabolism was also suggested by a proteomic analysis of zmpste24 -/-cells. 53 A unifying model can be proposed in which oxidative stress, regardless of the cause, affects lamins proteins functions and/or levels, resulting in both alteration of nuclear envelop structure and in loss of redox control, which amplify the oxidative stress. In agreement with this model, it has recently been reported that the tail domain of lamin A is a target of oxidative damage, and its irreversible oxidation led to a loss of lamin A function and entry into senescence.…”
Section: Acknowledgmentsmentioning
confidence: 99%